Dickkopf-1 is regulated by the mevalonate pathway in breast cancer - Rachner, Tilman D (BioMed Central, 2014)
INTRODUCTION: Amino-bisphosphonates and statins inhibit the mevalonate pathway, and may exert anti-tumor effects. The Wnt inhibitor dickkopf-1 (DKK-1) promotes osteolytic bone lesions by inhibiting osteoblast functions and has been implicated as an adverse marker in multiple cancers. We assessed the effects of mevalonate pathway inhibition on DKK-1 expression in osteotropic breast cancer. METHODS: Regulation of DKK-1 by bisphosphonates and statins was assessed in human breast cancer cell lines, and the role of the mevalonate pathway and downstream targets was analyzed. Moreover, the potential of breast cancer cells to modulate osteoblastogenesis via DKK-1 was studied in mC2C12 cells. Clinical relevance was validated by analyzing DKK-1 expression in the tissue and serum of women with breast cancer exposed to bisphosphonates. RESULTS: DKK-1 was highly expressed in receptor-negative breast cancer cell lines. Patients with receptor-negative tumors displayed elevated levels of DKK-1 at the tissue and serum level compared to healthy controls. Zoledronic acid and atorvastatin potently suppressed DKK-1 in vitro by inhibiting geranylgeranylation of CDC42 and Rho. Regulation of DKK-1 was strongest in osteolytic breast cancer cell lines with abundant DKK-1 expression. Suppression of DKK-1 inhibited the ability of breast cancer cells to block WNT3A-induced production of alkaline phosphates and bone-protective osteoprotegerin in preosteoblastic C2C12 cells. In line with the in vitro data, treatment of breast cancer patients with zoledronic acid decreased DKK-1 levels by a mean of 60% after 12 months of treatment. CONCLUSION: DKK-1 is a novel target of the mevalonate pathway that is suppressed by zoledronic acid and atorvastatin in breast cancer.